2013
DOI: 10.1093/hmg/ddt514
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of muscle strength in dystrophic muscle by angiotensin-1-7 through inhibition of TGF-β signalling

Abstract: Duchenne muscular dystrophy (DMD) is the most common inherited neuromuscular disease, and is characterized by the lack of dystrophin, muscle wasting, increased transforming growth factor (TGF)-β Smad-dependent signalling and fibrosis. Acting via the Mas receptor, angiotensin-1-7 [Ang-(1-7)], is part of the renin-angiotensin system, with the opposite effect to that of angiotensin II. We hypothesized that the Ang-(1-7)/Mas receptor axis might protect chronically damaged tissues as in skeletal muscle of the DMD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 144 publications
(183 citation statements)
references
References 56 publications
13
163
3
4
Order By: Relevance
“…In contrast to the present study, Ferreira et al showed an improved cardiac function, indicated by elevated dp/dt anddp/dt and furthermore, an attenuation of the isoproterenolinduced cardiac fibrosis in transgenic rats. Previous studies also indicated an antifibrotic action of Ang(1-7) in vitro and in vivo (Santos et al, 2004;Ferreira et al, 2010;Dong et al, 2012;McCollum et al, 2012;Acuña et al, 2014). In contrast to these findings, the present study revealed no antifibrotic effect of Ang(1-7) in a transgenic rat model.…”
Section: Discussioncontrasting
confidence: 88%
“…In contrast to the present study, Ferreira et al showed an improved cardiac function, indicated by elevated dp/dt anddp/dt and furthermore, an attenuation of the isoproterenolinduced cardiac fibrosis in transgenic rats. Previous studies also indicated an antifibrotic action of Ang(1-7) in vitro and in vivo (Santos et al, 2004;Ferreira et al, 2010;Dong et al, 2012;McCollum et al, 2012;Acuña et al, 2014). In contrast to these findings, the present study revealed no antifibrotic effect of Ang(1-7) in a transgenic rat model.…”
Section: Discussioncontrasting
confidence: 88%
“…Fibrous tissues may prevent normal tissue recovery, particularly in the muscle where fibrosis has been shown to lead to progressive skeletal muscle injury, for example in Duchenne's muscular dystrophy (Acuna et al, 2014). Previous work has suggested that PDGFRβ+ pericytes contribute to scar formation (Arimura et al, 2012) and express fibroblast-associated markers (such as collagen IV, fibronectin and fibroblast surface proteins).…”
Section: Tissue Fibrosismentioning
confidence: 99%
“…However, the instability of Ang-(1-7) restricts efficient oral or injected administration. 11,19 A new delivery method is needed that increases the half-life and improves the bioavailability of this peptide in target tissues.…”
Section: Introductionmentioning
confidence: 99%